EXECUTIVE ASPECT OF THE MUSLIM CONCEPT OF SOVEREIGNTY A CRITICAL ANALYSIS ON UMAR'S ASSURANCE OF AMAN TO THE PEOPLE OF AELIA. (2012) - YATIBAN, AMINURRAASYID; RAHMAN, FATIMATUZZAHRA ABD
No abstract available